Comparison of Mean Blood Loss in Cesarean Delivery Treated with Combined Oxytocin Misoprostol Versus Oxytocin Alone - Iftikhar, Ayesha; Shaheen, Shazia (Indus Journal of Bioscience Research, 2025)
Objectives: To compare the mean blood loss in cesarean deliveries treated with combined intravenous oxytocin and sublingual misoprostol versus oxytocin alone. Study Settings: Department of Obstetrics and Gynecology, Allied Hospital, Faisalabad. Duration of Study: Following approval from the College of Physicians and Surgeons Pakistan (CPSP). Data Collection: A randomized controlled trial was conducted involving 228 term pregnant women undergoing cesarean section. Participants were randomly allocated into two groups: Group A received 200 µg misoprostol plus 5 IU IV oxytocin, and Group B received oxytocin alone (5 IU IV bolus followed by 15 IU infusion). Blood loss was estimated using hematocrit changes measured pre- and 24 hours postoperatively. Results: The mean blood loss was lower in Group A (235.55 ± 99.27 mL) compared to Group B (263.91 ± 139.17 mL) (p = 0.078). Among patients with BMI >25 kg/m², the reduction in blood loss in Group A was statistically significant (p = 0.008). No significant differences were observed in hemoglobin or hematocrit levels between the groups overall. Conclusion: The combination of misoprostol and oxytocin during cesarean section is associated with reduced blood loss compared to oxytocin alone, particularly in women with elevated BMI. This synergistic approach may offer clinical benefits in high-risk populations.